Anxiety of Preschool Children Undergoing Hospitalization - Ginting, Amnita; Sembiring, Friska (Global Health Science Group, 2024)
Hospitalization often creates traumatic and stressful events for children and families. The stressors that children can experience related to hospitalization can produce various reactions. In addition to the physiological effects of health problems, the effects of hospitalization on children include anxiety and fear, separation anxiety and loss of control. Anxiety that occurs in children cannot be ignored, if it is not treated immediately it will cause the child to reject treatment and medication. The aim of this study was to examine the anxiety of preschool aged children (3-6 years) undergoing hospitalization in the children's room at Santa Elisabeth Hospital, Medan. Descriptive research design with accidental sampling technique, the number of respondents was 73 people, the questionnaire used was SCASS anxiety for preschool children. The research results showed that the highest level of anxiety was in the severe category, 49 people (67,1%) and the lowest was in the moderate category, 24 people (32,9%). So it can be concluded that the anxiety level of preschool children undergoing hospitalasia is in the severe category because the children feel afraid of the hospital atmosphere, afraid of the treatment provided, children always cry when their parents are not nearby, cry and are afraid when they see doctors and nurses, cry seeing the syringe by the nurse. It is hoped that nurses will continue to accompany children during hospitalization to reduce anxiety in children.